Enhanced electrical and thermal conductivities of silicon oxycarbide nanocomposites containing carbon nanofibers. (November 2018) - Mazo, M.A.; Tamayo, A.; Caballero, A.C.; Rubio, J.
Abstract: Novel silicon oxycarbide-carbon enriched composites (SiOC-C) were prepared from mixtures of SiOC and different amounts of carbon nanofibers (CNF) (0–10%) sintered through spark plasma sintering at 1500 °C. During sintering, the SiOC matrix experiences a rearrangement to SiO2, SiC and C, and the growth of SiC wires within the material which produce epitaxial graphene-like carbon flakes with AB stacking. Small additions of CNFs (0.5–1%) promote the generation of large amounts of β-SiC which produce more graphene-like carbon. When large amounts of CNFs are added graphene-like carbon and also huge entanglements of turbostratic carbon are formed widespread all over the SiOC-C material. These facts deeply influenced the observed properties. Small additions of CNFs (0.5–1%) produce an improvement of the thermal conductivity of 30% and an enhancement of three orders of magnitude in the electrical conductivity (2.44 × 10 −3 to 1.82 Sm -1 ) mainly due to a great increase in both the crystallite size and structural order of SiC and also the presence of graphene-like carbon homogenously dispersed within the SiOC matrix. Further additions of CNFs (10%) continue increasing both thermal and electrical conductivities (40% and 100 Sm -1, respectively) but such increases are less effectively by the presence of entanglements of turbostratic carbon. Graphical abstract: Image